PENGARUH MEDIA PASIR WARNA TERHADAP KEMAMPUAN MENGENAL LAMBANG BILANGAN ANAK USIA 5-6 TAHUN DI TK ISLAM INAYAH KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU - Sa’adiyah Sa’adiyah; Ria Novianti; Hukmi Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrak: The purpose of this study was to determine the effect of the use of color sand media on the ability to recognize the symbol of numbers of children aged 5-6 years in Islam Inayah Kindergarten Marpoyan Damai District, Pekanbaru City. This study used an experimental method with design one group pretest-posttest. The population and sample in this study were 10 children, and the data collection techniques used are observation. The data analysis technique in this study used the t-test with the help of SPSS for Windows Release 23.0. The hypothesis in this study is that there is an effect of the use of color sand media on the ability to recognize the number symbols of children aged 5-6 years in Islam Inayah Kindergarten Marpoyan Damai District, Pekanbaru City. Based on the data analysis, it was found that tcount= 21,894 > tttable= 6,305 with Sig. (2-tailed) = 0,000. Due to Sig <0.05, it can be concluded that there are differences in the ability to recognize the symbol of the number of children aged 5-6 years before and after treatment. It can be interpreted that there is an effect of giving color sand treatment to the ability to recognize the symbol of the number of children aged 5-6 years in Islam Inayah Kindergarten Marpoyan Damai District, Pekanbaru City, amounting to 58.16%Key Words: Color sand media, the ability to recognize number symbols